Efficient cell factories for the production of N‐methylated amino acids and for methanol‐based amino acid production. Issue 8 (30th April 2022) - Irla, Marta; Wendisch, Volker F.
Summary: The growing world needs commodity amino acids such as L‐glutamate and L‐lysine for use as food and feed, and specialty amino acids for dedicated applications. To meet the supply a paradigm shift regarding their production is required. On the one hand, the use of sustainable and cheap raw materials is necessary to sustain low production cost and decrease detrimental effects of sugar‐based feedstock on soil health and food security caused by competing uses of crops in the feed and food industries. On the other hand, the biotechnological methods to produce functionalized amino acids need to be developed further, and titres enhanced to become competitive with chemical synthesis methods. In the current review, we present successful strain mutagenesis and rational metabolic engineering examples leading to the construction of recombinant bacterial strains for the production of amino acids such as L‐glutamate, L‐lysine, L‐threonine and their derivatives from methanol as sole carbon source. In addition, the fermentative routes for bioproduction of N ‐methylated amino acids are highlighted, with focus on three strategies: partial transfer of methylamine catabolism, S ‐adenosyl‐L‐methionine dependent alkylation and reductive methylamination of 2‐oxoacids. Abstract : Methanol is a reduced form of carbon dioxide that can be utilized by methylotrophic microorganisms. In this review, we review on how this feedstock, that does not have competing uses in food or feed, serves amino acid fermentation processes.